Neoascotaiwania aquatica sp. nov. from a freshwater habitat in Yunnan Province, China - Yang, Lin; Bao, Dan-Feng; Luo, Zong-Long; Su, Xi-Jun; Su, Hong-Yan (Phytotaxa, 2022)
During an investigation of freshwater fungi from the Greater Mekong Subregion, a Bactrodesmium-like taxon was collected from a freshwater habitat in Yunnan Province, China. Phylogenetic analysis of combined LSU, SSU, ITS, TEF1-α and RPB2 sequence data placed the new isolate, Neoascotaiwania aquatica, in the genus Neoascotaiwania within Savoryellaceae. The new taxon is distinguished from other Neoascotaiwania species by its semi-macronematous, uniseptate, subhyaline to pale brown conidiophores and fusiform, 2-septate conidia.